Eichhornia crassipes (Water Hyacinth): Significance and Its Control - Mathiventhan, T.; Jayasingam, T. (Recent Progress in Plant and Soil Research Vol. 4, 2021)
Eichhornia crassipes, commonly known as Water hyacinth, is an aquatic plant. It has been listed as one of the worst weeds mostly in the tropics and subtropics and listed as Invasive Alien Species (IAS) in Sri Lanka. Many efforts had been made to eradicate this species, but Eichhornia still shows wide distribution, posing a tremendous threat to aquatic biota in many inland water systems. The study would investigate to control of the species by using salinity as a tool. Experiments were set up to study the growth of the species and to study the role of salinity on the growth and survival of the species. Growth experiment was conducted by means of measuring the growth of the species in terms of the production of leaves in fresh water tanks for a period of three months; salinity experiments were setup using various salinity levels of 1, 2, 3, 4, 5, 6, 7, 10, 15 and 20 ppt. The control treatment was the water with zero salinity. Two plants were placed in each tray and observed over the next 16 days. The number of leaves increases with time up to 40 days. It showed a sudden declined in the production of leaves, 55 days onwards. Leaves that were produced were getting rotten after 40 days onwards. The experiment showed that the E. crassipes survive at 0 ppt saline water throughout the experiment, the appearance of the percentage of green shoots existed as 100%. The shoots were becoming brown and subsequently dead after 4 days of the experiment at the salinity level 7 ppt. The plants showed a gradual decline in their appearance of green shoot between 0 and 6 ppt with the increasing salinity over time. Salinity would be an option to control the water hyacinth but its practical applicability in the larger water bodies would make a great challenge.